Exploring Chinese outbound exhibitors' motivational factors and characteristics to U.S. exhibition market. Issue 8 (3rd August 2017) - Wang, Yingchuan; Lee, Myong Jae; Huh, Chang
ABSTRACT: For exhibitions to have sustainable success, they must attract enough high-quality exhibitors. As China has opened up and grown economically in the past several decades, more Chinese exhibitors are participating in exhibitions worldwide, and United States exhibitions are among their top destination. To examine what motivates the participation of this growing group, this study conducted a self-administered survey among Chinese outbound exhibitors who have attended exhibitions in the United States. With the help from the Chinese exhibition organizers, a questionnaire survey was distributed to Chinese exhibitors having participating in U.S.-based trade fairs in the past 12 months via email for collecting data. An exploratory factor analysis and a series of ANOVA tests were carried out to examine the Chinese exhibitors' characteristics. The results of the 314 usable responses showed that exhibitors with their characteristics differed significantly in the five motivational dimensions. These dimensions relate to motivations in social contacts and networking, sales, incentive, "guanxi, " and competition. The findings have marketing implications for exhibition organizers in both the United States and China for recruiting and retaining Chinese exhibitors.